Competing for Supremacy: The Origins of Shakespeare Studies in Japan - Uchimaru, Kohei (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This paper reveals that Shakespeare studies in Japan originated through competing notions of literary studies. Traditional Japanese ideas about literature differed markedly from Anglophone ones, which focused on grammatical and literary-historical facts based on the notion of Shakespeare’s universal appeal. Their principles were contested by Sôseki Natsume, who questioned Shakespeare’s vaunted universality between the 1900s and the 1910s. Although specialist scholars began forming Shakespeare as an object of disinterested study in the 1920s, it was contested again by some reflective scholars who wished to employ Shakespeare as a means of liberal education. These contests for supremacy spawned divergent origins of Shakespeare studies in Japan.